Analysis of the transition between dry and wet days through third-order Markov chains - Keller Filho, Thadeu; Zullo Junior, Jurandir; de Rezende Lima, Paulo Roberto Schubnell (Pesquisa Agropecuaria Brasileira, 2006)
The aim of this work was to verify if the occurrence of dry and wet days are conditionally dependent on the sequences of the dry and wet three preceding days, in a rainfall homogeneous area, using the nonhomogeneous third-order Markov chains. The results showed that daily transition probabilities can be properly estimated from two-month aggregate data, and then adjusted by means of sinusoidal functions. Besides, it was evidenced that everyday rain events in that area are conditionally dependent on the sequences of the dry and wet three days previous to occurrences. The third-order nonhomogeneous Markov chains are an important instrument for the analysis of the dependence between sequences of dry and wet days in certain areas.